Validation analysis of Global Health Security Index (GHSI) scores 2019. Issue 10 (26th October 2020) - Boyd, Matthew J; Wilson, Nick; Nelson, Cassidy
Abstract : Introduction: The COVID-19 pandemic powerfully demonstrates the consequences of biothreats. Countries will want to know how to better prepare for future events. The Global Health Security Index (GHSI) is a broad, independent assessment of 195 countries' preparedness for biothreats that may aid this endeavour. However, to be useful, the GHSI's external validity must be demonstrated. We aimed to validate the GHSI against a range of external metrics to assess how it could be utilised by countries. Methods: Global aggregate communicable disease outcomes were correlated with GHSI scores and linear regression models were examined to determine associations while controlling for a number of global macroindices. GHSI scores for countries previously exposed to severe acute respiratory syndrome (SARS), Middle East respiratory syndrome and Ebola and recipients of US Global Health Security Agenda (GHSA) investment were compared with matched control countries. Possible content omissions in light of the progressing COVID-19 pandemic were assessed. Results: GHSI scores for countries had strong criterion validity against the Joint External Evaluation ReadyScore (rho=0.82, p<0.0001), and moderate external validity against deaths from communicable diseases (−0.56, p<0.0001). GHSI scores were associated with reduced deaths from communicable diseases ( F (3, 172)=22.75, p<0.0001). The proportion of deaths from communicable diseases decreased 4.8% per 10-point rise in GHSI. Recipient countries of the GHSA (n=31) and SARS-affected countries (n=26), had GHSI scores 6.0 (p=0.0011) and 8.2 (p=0.0010) points higher than matched controls, respectively. Biosecurity and biosafety appear weak globally including in high-income countries, and health systems, particularly in Africa, are not prepared. Notably, the GHSI does not account for all factors important for health security. Conclusion: The GHSI shows promise as a valid tool to guide action on biosafety, biosecurity and systems preparedness. However, countries need to look beyond existing metrics to other factors moderating the impact of future pandemics and other biothreats. Consideration of anthropogenic and large catastrophic scenarios is also needed.